FRI0124 FACTORS ASSOCIATED WITH PERSISTENT DRUG-FREE REMISSION IN PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Valor, Larissa; Hagen, Melanie; Reiser, Michaela; Kleyer, Arnd; Hartmann, Fabian; Manger, Bernhard; Schett, Georg; Rech, Jürgen; Tascilar, Koray; ,
Abstract : Background: Persistent drug-free remission of RA is a condition that is close to "cure" of the disease. However, long-term drug-free remission is considered to be rare and very challenging to reach. Also, little data are available that report how often persistent drug-free remission can be achieved and what kind of clinical characteristics are associated with such state. Objectives: To evaluate factors associated with persistent drug-free remission in patients with rheumatoid arthritis Methods: We analyzed the long-term observational follow-up phase of the randomized controlled RETRO (REduction of Therapy in RA Patients in Ongoing Remission) study on tapering and stopping of DMARDS in RA patients in stable remission (DAS28-ESR <2.6) (1, 2). We included patients having completed the 1-year randomized controlled phase of RETRO, in which DMARD treatments were either continued, tapered or stopped. In the long-term extension, (i) patients who successfully stopped, continued DMARD stop, (ii) patients who relapsed in any of the 3 groups continued DMARD treatment, (iii) patients in the continuation arm remaining in remission underwent 50% DMARD tapering followed by stopping after 6 months if still being in remission and (iv) patients in the tapering arm remaining in remission underwent DMARD stop. We assessed the percentage of patients in persistent drug-free remission in the overall population and the three randomization groups, the probability of persistent drug-free remission in the intervention groups compared to controls adjusted by baseline aCCP, erosive changes and use of biologic DMARDs in a logistic regression model and the baseline characteristics associated with reaching persistent drug-free remission. Results: All 141 patients being in the long-term observational follow-up phase of the RETRO study for at least 1 year were analyzed. Among them DMARDs were initially continued (Control, n=38), tapered (Taper, n=50) or stopped (Taper/Stop n=53). 19/141 patients were lost to follow-up and the worst case scenario was assumed that all of them did not reach persistent drug-free remission. Median time after study entry (Q1-Q3) was 69 (37-96) months as by December 2018. Overall number of patients in drug-free remission was 34/141 (24.1%), 10/38 (26%) in the control group, 6/50 (12%) in the taper group and 18/53 (34%) in the taper/stop group. After adjustment for baseline risk factors in the likelihood to reach persistent drug-free remission between the groups (OR:0.76, 95%CI: 0.29-1.99) was highly uncertain. Positive ACPA (OR: 3.38, 1.01 – 11.31) and erosive-state (3.05, 1.32 – 7.06) at baseline were associated with a lower likelihood to reach persistent drug-free remission. Conclusion: These data show that persistent drug-free remission can be reached in a subset of RA patients following a structured DMARD tapering approach after being in stable long-term DMARD control. References: [1] Haschka J, et al. Relapse rates in patients with rheumatoid arthritis in stable remission tapering or stopping antirheumatic therapy: interim results from the prospective randomised controlled RETRO study. Ann Rheum Dis. 2016 Jan;75(1):45-51. [2] Rech J, et al. Prediction of disease relapses by multibiomarker disease activity and autoantibody status in patients with rheumatoid arthritis on tapering DMARD treatment. Ann Rheum Dis 2016;75:1637-44. Disclosure of Interests: Larissa Valor: None declared, Melanie Hagen: None declared, Michaela Reiser: None declared, Arnd Kleyer Grant/research support from: Lilly, Consultant for: Lilly, Speakers bureau: Abbvie, Fabian Hartmann: None declared, Bernhard Manger: None declared, Georg Schett: None declared, Jürgen Rech Grant/research support from: Bristol-Myers Squibb and Celgene (greater than 10, 000), Consultant for: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000), Speakers bureau: Bristol-Myers Squibb, Celgene, Chugai, GlaxoSmithKline, Janssen, Eli Lilly, Novartis, Roche, Sanofi Aventis, and UCB (in total more than 10, 000), Koray Tascilar: None declared